Constructive Dismissal Claims of Senior Management Employees in Malaysia: A Critical Discourse Analysis - Tahirah Manesah, Abu Bakar (2024)
This thesis delved into the significant yet underexplored issue of constructive dismissal (CD) within the senior management level. As the second layer of management, senior management employees play a pivotal role in shaping and maintaining an organisation's culture. Their departure, particularly when it is a result of constructive dismissal, can have far-reaching implications for the organisation. The primary objective of this research was to address the existing gap in knowledge by scrutinising the perceptions and triggers of CD claims made by senior management employees in Malaysia. Additionally, it sought to understand the stance of the Malaysian Courts on these matters. The research methodology involved purposive sampling of award reports from the legal databases operated by the Current Law Journal (CLJ). Data extracted from these reports were then coded using Critical Discourse Analysis (CDA) and Thematic Analysis (TA). These analytical methodologies were applied within the theoretical framework of the Social Exchange Theory, providing a comprehensive lens through which the data were scrutinised. The findings of this research revealed that the primary reason claimants resigned from their positions was a breach of fundamental contract terms, triggered by what was referred to as the "Brick Wall circumstance" - a situation where the employer completely disregarded the claimants’ grievances. The Courts however did not concur with the claimants in every case. The study therefore concludsed that intervention and mediation by Human Resources (HR) might be necessary to identify potential CD risks and to mitigate these risks. The findings of this study aimed to deepen HR practitioners' understanding of the CD doctrine and provided a solid foundation for future research on the subject. This research contributed to the field of HR management by offering a nuanced understanding of CD, particularly within senior management, and its implications for organisational culture and stability.